(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: In today’s fast-evolving work environment, employees must continuously upskill and reskill to remain competitive. Organizations in Kathmandu Valley are increasingly emphasizing learning initiatives. Understanding employees’ behavioral intention toward these programs helps identify key drivers, such as knowledge acquisition and technical training, to design effective workforce development strategies. Purpose: The purpose of this study is to determine employee’s behavior intention towards upskilling and reskilling in Kathmandu Valley. Design/methodology /approach: The study uses explanatory research design, TAM theory uses, Convenience sampling is used, Self-administered questionnaire is used and modified, Kobo toolbox is used for data collection, Kathmandu Valley is the study area, Smart PLS 4.0 is used for data analysis, Descriptive and Inferential data analysis techniques were used. Findings: The findings show that most employees are aware of upskilling and reskilling and view them as essential for career growth. Knowledge acquisition (β = 0.374, p < 0.05) and technical training (β = 0.452, p < 0.05) significantly influenced employees’ attitudes, while attitude strongly predicted behavioral intention to learn (β = 0.378, p < 0.05). Top management support (β = 0.034, p = 0.432) and subjective norms (β = 0.039, p = 0.298) were not significant predictors of attitude. Mediation results further confirmed attitude as a key intervening variable linking organizational and social factors with learning intention. Conclusion: According to this study, Knowledge Acquisition and Technical Training has a significant relationship with attitude, Attitude and Behavior Intention to Learn has a significant relation and Attitude has mediating effect independent variable (Top Management Service, Technical Training and Subjective Norms) and Behavior Intention to Learn Upskilling and Reskilling. Keywords: TAM, Microsoft Excel, Adoption/Acceptance, SEM, Organization.